2008
DOI: 10.1080/10582450802161853
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization and Indirect Burden among Families of Pediatric Patients with Chronic Pain

Abstract: Objectives: Chronic pain is associated with substantial direct and indirect costs in adulthood. Chronic pain problems are also common in childhood, but little is known about the costs of pédiatrie chronic pain and its treatment. The objectives of this study were to examine and describe healthcare utilization and indirect burden among pédiatrie chronic pain patients and their families.Methods: Participants were parents of 75 pédiatrie patients with daily or almost daily pain for at least three months, seen at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 16 publications
(5 reference statements)
1
63
1
3
Order By: Relevance
“…34 Items included the number of outpatient visits (primary care, specialty care, and counselor/psychologist visits) and emergency department visits within the past year.…”
Section: Health Care Utilizationmentioning
confidence: 99%
“…34 Items included the number of outpatient visits (primary care, specialty care, and counselor/psychologist visits) and emergency department visits within the past year.…”
Section: Health Care Utilizationmentioning
confidence: 99%
“…8 Early pain management intervention can reduce pain duration, pain-related disability, and thus health care expenditures. [9][10][11] However, recent surveys have revealed unacceptably high levels of undertreatment and intolerably long wait times (often >1 year) to access appropriate chronic pain care in Canada. 11,12 Moreover, in 2007, Peng et al reported the status of dedicated multidisciplinary pediatric chronic pain clinics in Canada and found only five, leaving many provinces and regions without access to subspecialty pediatric chronic pain care.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] However, recent surveys have revealed unacceptably high levels of undertreatment and intolerably long wait times (often >1 year) to access appropriate chronic pain care in Canada. 11,12 Moreover, in 2007, Peng et al reported the status of dedicated multidisciplinary pediatric chronic pain clinics in Canada and found only five, leaving many provinces and regions without access to subspecialty pediatric chronic pain care. 13 In 2013, an unpublished updated review concluded that this number had increased to eight 14 and, since then, the number of Canadian pediatric chronic pain clinics has only increased to ten.…”
Section: Introductionmentioning
confidence: 99%
“…Šiai kompleksinei sveikatos problemai reikia visapusiško požiūrio į gydymą. Vaiko skausmas susijęs su tiesioginėmis ir netiesioginėmis lėšų sąnaudomis, skirtomis sveikatos priežiūrai, nes dažnai tėvai tam, kad galėtų rūpintis lėtinį skausmą patiriančiu vaiku, priversti mesti darbą, prarasdami darbo užmokestį [32,33]. Lygindami suaugusiųjų ir vaikų, kenčiančių nuo lėtinio skausmo, literatūroje aptinkamus duomenis, randame, kad vaikams, patiriantiems lėtinį skausmą, reikia daugiau sveikatos priežiūrai skiriamų resursų [34], jie dažnai patiria komorbidinių psichologinių ir socialinių problemų [27,35].…”
Section: Lėtinio Skausmo Sukeltos Socialinės Problemosunclassified